2018
DOI: 10.1007/s11244-018-1095-y
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of NH3-TPD Profiles from Cu-CHA Using First-Principles Calculations

Abstract: Temperature-programmed desorption (TPD) with ammonia is widely used for zeolite characterization revealing information on acidity and adsorption sites. The interpretation of TPD measurements is, however, often challenging. One example is the NH 3 -TPD profile from Cu-chabazite (Cu-CHA) which generally is deconvoluted in three peaks with contributions from NH 3 on Lewis acid sites, copper sites and Brønsted acid sites. Here, we use density functional theory calculations combined with kinetic simulations to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 42 publications
3
42
1
Order By: Relevance
“…The intensity of these peaks corresponding to strong acid sites for high copper loadings is found to be reduced at high temperature 14 . But the moderate acid sites of high copper loading have increased by many folds in the moderate temperature region 58,59 . In short, it can be observed that the copper incorporation into the zeolite structure resulted in a considerable boosting in the acidity of the surface of all synthesized samples.…”
Section: Resultsmentioning
confidence: 83%
“…The intensity of these peaks corresponding to strong acid sites for high copper loadings is found to be reduced at high temperature 14 . But the moderate acid sites of high copper loading have increased by many folds in the moderate temperature region 58,59 . In short, it can be observed that the copper incorporation into the zeolite structure resulted in a considerable boosting in the acidity of the surface of all synthesized samples.…”
Section: Resultsmentioning
confidence: 83%
“…Based on the shape of the NH 3 -TPD profiles it can be concluded that the investigated samples contain acid centers of different strengths. The traditional classification [ 28 ] describes the existence of two kinds of acid centers: weak acid centers assigned to low-temperature peaks (below 400 °C) and strong acid centers ascribed to high-temperature peaks (above 400 °C). The low-temperature peaks refer to desorption of ammonia from weakly acidic silanol groups and weak Lewis acid centers, while high-temperature peaks correspond to desorption of ammonia from strong Brønsted and Lewis acid sites [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…22 2.3.1 Calculated methanol desorption profiles. The theoretical methanol desorption profiles were calculated assuming an isolated, independent site where adsorption and desorption of methanol occur, 45,46 i.e. the process:…”
Section: Theoretical Methodsmentioning
confidence: 99%